1958
DOI: 10.5962/bhl.title.6560
|View full text |Cite
|
Sign up to set email alerts
|

Fishes of Maine / W. Harry Everhart.

Abstract: the eels and others have become flattened from side to side as the basses and are known as compressed. Fishes of Maine are either rounded or compressed in body form. Covering the fish externally is a layer of mucus secreted by the glands of the skin. This mucus protects fish from external infection. Fishermen have long been cautioned to wet their hands before handling fish which they intend to return to the water. Handling with dry hands would remove a large amount of this protective covering and leave the fis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…JFCs in particular, with their narrow distribution of inclinations, represent a distinct family of objects with a specific reservoir. Early attempts to reconcile the idea that JFCs come from the Oort cloud showed that, although possible, such a dynamical path is in extreme inefficient at producing low inclination comets in shortperiod orbits, thus showing that such scenario is unlikely to be viable (Everhart 1972;Joss 1973;Fernandez & Gallardo 1994). In a seminal paper Fernandez (1980) (working on the ideas of Edgeworth 1949;Kuiper 1951Kuiper , 1974 was the first to numerically examine the possibility of the existence of a comet belt beyond Neptune in connection with the origin of the SPCs.…”
Section: Introductionmentioning
confidence: 99%
“…JFCs in particular, with their narrow distribution of inclinations, represent a distinct family of objects with a specific reservoir. Early attempts to reconcile the idea that JFCs come from the Oort cloud showed that, although possible, such a dynamical path is in extreme inefficient at producing low inclination comets in shortperiod orbits, thus showing that such scenario is unlikely to be viable (Everhart 1972;Joss 1973;Fernandez & Gallardo 1994). In a seminal paper Fernandez (1980) (working on the ideas of Edgeworth 1949;Kuiper 1951Kuiper , 1974 was the first to numerically examine the possibility of the existence of a comet belt beyond Neptune in connection with the origin of the SPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to identify the Centaur sources have largely focused on dynamical models of the potential source regions. Early studies to identify a source region for the short period comets suggested that the long period comets (originating from the nearly isotropic distant Oort Cloud) could be captured into short period orbits by means of planetary perturbations, and that the higher capture probabilities at low inclinations could explain the prograde, low inclinations of the short period comets (Everhart 1972). But Fernandez (1980) and Duncan et al (1988) showed that Everhart's mechanism is a very inefficient way to produce Centaurs and short period comets from Oort Cloud comets, suggesting that a more proximate, lowerinclination population just beyond Neptune would be a more likely source region.…”
Section: Introductionmentioning
confidence: 99%
“…Fernandez (1980) suggested that such a belt of distant icy planetesimals could serve as the source of the short-period comets and would be more dynamically efficient than evolving long-period comets inward from the Oort cloud as first suggested by Newton (1893; also Everhart 1972Everhart , 1977. Duncan et al (1988) confirmed this with dynamical simulations which showed that a cometary source with a low initial inclination distribution was far more consistent with the observed orbits of the short-period comets than the randomly distributed inclinations of comets in the Oort cloud.…”
Section: Introductionmentioning
confidence: 99%